Simultaneous alcoholic and acetic acid fermentation in pineapple juice with co-culture of yeast and acetic acid bacteria - Chanprasartsuk, On-ong; Jaroenmaneesap, Kittaphat; Wongjinda, Krittapoj (Food Agricultural Sciences and Technology, 2023)
Co-culture of yeast and acetic acid bacteria (AAB) is consortium which be useful on food and beverage fermentation. The various fermented beverages; alcoholic and non-alcoholic drinks, are obtained by these microbial communities and their interactions. The activities of co-culture of yeasts and acetic acid bacteria during pineapple juice fermentation, including the growth of starters, physicochemical and key compounds changes during pineapple juice fermentation were investigated. The specific characteristics of initial pineapple juice was appropriate for using as a raw material for single and dual yeast and AAB fermentation with no chaptalization. The adding of AAB could encourage the growth and ethanol production of allochthonous and autochthonous yeasts during pineapple juice fermentation, concurrently, the growth of AAB slowly decreased throughout the fermentation. In order to better understand the relationship between yeast and AAB during pineapple juice fermentation. The influence of pineapple juice properties on the growth of AAB during pineapple fermentation was further investigated.